2021
DOI: 10.3389/fvets.2020.608348
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Water Temperature Related Physiologically Based Pharmacokinetic Model for Enrofloxacin and Its Metabolite Ciprofloxacin in Rainbow Trout

Abstract: Enrofloxacin (ENR) has been approved for the treatment of infections in aquaculture, but it may cause tissue residue. This research aimed to develop and validate a water temperature related PBPK model, including both ENR and ciprofloxacin (CIP), in rainbow trout, and to predict further their residue concentrations and the withdrawal periods for ENR at different water temperatures. With the published concentrations data, a flow-limited PBPK model including both ENR and CIP sub-models was developed to predict EN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Initially, we used a two‐compartment model to simulate the absorption of orbifloxacin after intramuscular injection; however, satisfactory predictions could not be obtained, so we finally chose the current one‐compartment model (Yang et al, 2013). A water temperature‐related PBPK model was established in rainbow trout (Yang et al, 2021), which could adequately predict the concentrations of enrofloxacin and its metabolite ciprofloxacin in rainbow trout reared at a wide range of water temperatures (5–16°C). Essentially, the current model was also temperature‐related because the cardiac output depended on water temperature (Barron et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, we used a two‐compartment model to simulate the absorption of orbifloxacin after intramuscular injection; however, satisfactory predictions could not be obtained, so we finally chose the current one‐compartment model (Yang et al, 2013). A water temperature‐related PBPK model was established in rainbow trout (Yang et al, 2021), which could adequately predict the concentrations of enrofloxacin and its metabolite ciprofloxacin in rainbow trout reared at a wide range of water temperatures (5–16°C). Essentially, the current model was also temperature‐related because the cardiac output depended on water temperature (Barron et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological and anatomical parameters were derived from previous fish PBPK models (Yang et al, 2013(Yang et al, , 2021 and presented in Table 2. The tissue weight and blood flow were abbreviated to V cx and Q cx , respectively, and expressed as BW and cardiac output fractions.…”
Section: Model Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, similarly to what Yang et al (2021) reported, firstly the 1000 virtual individuals with different physiological parameters were simulated, by giving a default 10% coefficients of variance (CVs) to the sensitive parameters [ 20 ]. However, the calculated WTs in the edible tissues were significantly shorter than the measured WTs.…”
Section: Discussionmentioning
confidence: 99%
“…Then, these values were calculated, after rounding up to the next whole day, according to WT estimation criteria [ 17 ]. Reportedly, the WT values that were calculated by the EMA’s method could keep consistent with the values, using one MC simulation [ 20 , 23 ]. Therefore, using one MC analysis, with 1000 iterations for each tissue, is sufficient to predict the WTs of the ENR granules in tissues.…”
Section: Discussionmentioning
confidence: 99%